2001
DOI: 10.1021/ja002481s
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Titanium Phosphate Molecular Sieves with Ion-Exchange Capacity

Abstract: Novel open framework molecular sieves, titanium(IV) phosphates named, i.e., TCM-7 and -8 (Toyota Composite Materials, numbers 7 and 8), with new mesoporous cationic framework topologies obtained by using both cationic and anionic surfactants are reported. The (31)P MAS NMR, UV-visible absorption, and XANES data suggest the tetrahedral state of P and Ti, and stabilization of the tetrahedral state of Ti in TCM-7/8 is due to the incorporation of phosphorus (at Ti/P = 1:1) vis-à-vis the most stable octahedral stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
205
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(216 citation statements)
references
References 35 publications
9
205
1
1
Order By: Relevance
“…11 In addition, cobalt phosphates are of interest because of their magnetic properties. 12 Since the first amino-templated tetrahedral open framework cobalt phosphate [C 2 H 10 N 2 ]-[CoPO 4 ] was reported in 1994, much attention has been paid to this class of compounds. 13 Recently, our group successfully utilized ionic liquids (ILs) in the synthesis of metal, metal fluoride, and metal oxide nanomaterials for energy-related applications, for example, in catalysis or photonic materials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, cobalt phosphates are of interest because of their magnetic properties. 12 Since the first amino-templated tetrahedral open framework cobalt phosphate [C 2 H 10 N 2 ]-[CoPO 4 ] was reported in 1994, much attention has been paid to this class of compounds. 13 Recently, our group successfully utilized ionic liquids (ILs) in the synthesis of metal, metal fluoride, and metal oxide nanomaterials for energy-related applications, for example, in catalysis or photonic materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For determination of the dc magnetic susceptibility, a field of 0.1 T was used for the temperature-dependent measurement, and fields up to 7 T were used for the isothermal magnetizations at temperatures of 2, 5, 10, 20, and 30 K. The driving field in the ac measurements was 2 Oe, with frequencies ranging from 1 to 1000 Hz. 4 (OH) (0 ≤ y ≤ 2/3). 21 The competing phase, Co 2 PO 4 F (2), 22 crystallizes isostructurally with triplite (Mn 2 PO 4 F) 23 with the space group C2/c.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The absence of these vibration bands in the spectrum of P-TiO 2 suggested the removal of organic material after heating. However, an absorption band around 1090 cm -1 (characteristic frequency of PO 4 3− ) 28 appeared on the shoulder of −Ti−O−Ti vibration band in the spectrum of P-TiO 2 , which revealed that phosphorus might have been incorporated on the surface of nano titania. The result of EDX analysis also supported this finding.…”
Section: Characterization Of P-tiomentioning
confidence: 99%
“…[4,5]. Phosphate materials are well known to have a high affinity for living organisms and are therefore expected to be useful as white pigments in cosmetics.…”
Section: Introductionmentioning
confidence: 99%